2017
DOI: 10.1177/1933719116670036
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of SRA1 Regulates ER Expression and Attenuates the Growth of Stromal Cells in Ovarian Endometriosis

Abstract: Estradiol and its nuclear receptors, estrogen receptor (ER) α and ER-β, have important functions in endometriosis, and the transcriptional activity of these receptors is modulated by coactivators and corepressors. The steroid receptor RNA activator 1 (SRA1) produces SRA long noncoding RNA (lncRNA) and SRA protein (SRAP), which regulate ER expression at the RNA and protein levels in some hormone-dependent tumors via an alternative splicing event. However, only a few are reported on their expressions in endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 43 publications
1
20
1
Order By: Relevance
“…Although EMT is a frequently occurring benign disease, it is characterized by malignant behaviors including recurrence and metastasis ( 68 , 69 ). At present, various pharmacotherapies and other methods have been proposed to treat EMT ( 70 , 71 ). However, their usage has been limited due to strong and obvious adverse effects ( 65 , 72 ).…”
Section: Ccn1/cyr61 and The Female Reproductive Systemmentioning
confidence: 99%
“…Although EMT is a frequently occurring benign disease, it is characterized by malignant behaviors including recurrence and metastasis ( 68 , 69 ). At present, various pharmacotherapies and other methods have been proposed to treat EMT ( 70 , 71 ). However, their usage has been limited due to strong and obvious adverse effects ( 65 , 72 ).…”
Section: Ccn1/cyr61 and The Female Reproductive Systemmentioning
confidence: 99%
“…Wang et al [ 8 ] reported that lncRNA AC002454.1 can participate in the pathogenesis of endometriosis by regulating CDK6 to disrupt the cell cycle. Expression of lncRNA SRA has been found to be associated with expression of estrogen receptor alpha and proliferation of endometriotic stromal cells [ 11 ]. LncRNA H19 expression has recently been shown to decrease in eutopic endometrial tissues, and the restoration of H19 expression in endometriotic stromal cells can promote cell proliferation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are the most common noncoding RNAs and are involved in cell proliferation, differentiation, and apoptosis; all processes central in the pathobiology of endometriosis [21]. Some lnc-RNAs proposed as diagnostic markers of endometriosis include: H19 [22], CHL1-AS2 microRNA and Overcoming the Challenges of Their Use in the Diagnosis of Endometriosis DOI: http://dx.doi.org/10.5772/intechopen.91324 [23,24], AC002454.1 [25], lncRNA SRA (steroid receptor RNA activator) [26], MALAT-1 [27], and LINC01279 [28]. Results of a recent study revealed the lnc-RNA are carried in circulating extracellular vesicles in women with endometriosis [29].…”
Section: Candidate Clinical Markers Of Endometriosismentioning
confidence: 99%